PENERAPAN SI TAMPPAN BERBASIS KINERJA DI DINAS KUKM DAN PERINDAG KABUPATEN WONOGIRI - Etika Gustiana; Hery Sawiji; Tri Murwaningsih (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2022)
Abstract The purpose of this research is to find out the performance-based implementation of Si TAMPPAN at KUKM and Perindag Office Wonogiri. The research is a qualitative descriptive research using a case study approach. The sampling technique used is purposive sampling and snowball sampling. Data validation was obtained by methodological and sources triangulation. The results of the research shows: (1) Performance-based implementation of Si TAMPPAN at KUKM and Perindag Office Wonogiri in the form of: (a) Planning stage which includes: (1) socialization and training; (2) preparation of SKP; and (3) SKP approval; (b) activity uploads; (c) activity journal verification; (d) implementation results; (e) evaluation of information systems. (2) Obstacles in the implementation of Si TAMPPAN include: (a) dissemination of Si TAMPPAN was not maximal; (b) lack of IT mastery; (c) lack of facilities and infrastructure to support the implementation; (d) Si TAMPPAN's server is still having problems. (3) Efforts to overcome obstacles to the implementation of Si TAMPPAN include: (a) Re- dissemination of Si TAMPPAN to civil servants; (b) IT mentoring to civil servants who lack IT skills; (c) use more upgraded mobile phones and personal laptops; (d) make a statement letter and contact the super admin of Si TAMPPAN.